Isotretinoin for Cutaneous Sarcoidosis: A Potential Therapy - Oktarina, Caroline; Irawan, Yudo; Widaty, Sandra (Journal of Pakistan Association of Dermatologists, 2023)
Sarcoidosis is a chronic noncaseating granulomatous disorder with clinical manifestations involving various organs, including skin. The incidence of sarcoidosis reached 35.5 – 64 cases per 100,000 people in the United States while Dr. Cipto Mangunkusumo National Central General Hospital, Jakarta reported the incidence of cutaneous sarcoidosis of 0.07% in 2015-2019. Numerous treatment modalities have been developed for the treatment of sarcoidosis and steroid becomes the first-line treatment for sarcoidosis. However, cases of sarcoidosis recalcitrant towards steroid are often reported, leading to consideration of other medications with possible efficacy on sarcoidosis, one of which is isotretinoin. Isotretinoin plays a role in sarcoidosis through its effect on inhibiting Tumor Necrosis Factor (TNF) and enhancing the production of prostaglandin E2 (PGE2). Based on several studies reported, level of evidence (LoE) of isotretinoin for the management of cutaneous sarcoidosis is level IV. Therefore, albeit being quite potential for the management of cutaneous sarcoidosis, further studies are necessary to prove the effectiveness of isotretinoin.